NILAI-NILAI PENDIDIKAN AKHLAK DALAM PERSPEKTIF AL-QUR’AN (KAJIAN SURAH AL-HUJURAT AYAT 11-12) - Muhamad Khoirul Adzmi; Syamsuddin Syamsuddin (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Moral Education aims to guide students to be able to distinguish between good and bad. However, in this modern era, the moral crisis is increasingly visible, so it is necessary to strengthen moral education, so that students become an intelligent and civilized generation. The purpose of this research is to examine what are the values of moral education contained in Surah Al-Hujarat verses 11-12. This study uses a qualitative research approach with a type of library research. Furthermore, data collection is carried out through the interpretation of Surah Al-Hujarat verses 11-12, explaining its meaning, asbabun nuzul, and analyzing the value of moral education in these verses. The results of this study show that Surah Al-Hujarat verses 11-12 teach moral values to create a harmonious, peaceful, and respectful life among others. This is closely related to Islamic education, which plays an important role in instilling these values to form noble morals and create a superior and well-behaved generation.